Bahan Bakar Minyak Dari Berbagai Metode Konversi Sampah Plastik - Ibrahim, Masri; Machmud, M. Nizar; Ali, Masri (Journal of Engineering and Science, 2022)
The use of plastic and goods made of plastic have been rising in day to day. Increasing use of plastics is a consequence of the development of technology, industry and population. On one hand, the invention of plastic has a remarkable positive impact, because it has many advantages compared to other materials. But on the other hand, the plastic waste has negative impact that too worried, so its solutions need to be looked for. One of the alternative handling of plastic waste that currently extensively researched and developed is converting plastic waste into fuel. Converting plastic waste into fuel oil can be done with cracking process. There are three kinds of process that is hydro cracking, thermal cracking and catalytic cracking. Fuel oil produced from the cracking of plastic waste depending on the plastic type, cracking process used, catalyst type, pyrolisis temperature and condenser temperature.